Magnetic Dextran Nanoparticles That Bear Hydrophilic Porphyrin Derivatives: Bimodal Agents for Potential Application in Photodynamic Therapy. Issue 9 (5th May 2015) - Mbakidi, Jean‐Pierre; Brégier, Frédérique; Ouk, Tan‐Sothea; Granet, Robert; Alves, Sandra; Rivière, Eric; Chevreux, Sylviane; Lemercier, Gilles; Sol, Vincent
Abstract This study reports the chemical synthesis of a class of dextran superparamagnetic nanoparticles that bear hydrophilic porphyrin units covalently grafted by a click chemistry reaction in aqueous solution. Magnetic nanoparticles are used in magnetic resonance imaging (MRI) and hyperthermia, and the grafting of hydrophilic photosensitizers (PS) leads to elaborate new multifunctional platforms for potential diagnostic and targeted photodynamic therapy (PDT). The therapeutic potential for PDT of these nanoparticles is evaluated in vitro against the HaCaT cell line. The results show that these new multicharged nanomagnets—in particular, those that bear cationic porphyrins—show a significant uptake and an interesting photocytotoxic activity toward HaCaT cells. The whole series of these synthesized PS are massively incorporated inside HaCat cells and associated with mitochondria.